A randomized clinical trial of a new perioperative practice model on anxiety and health‐related quality of life in arthroplasty patients. Issue 4 (12th February 2021) - Pulkkinen, Maria; Jousela, Irma; Sintonen, Harri; Engblom, Janne; Salanterä, Sanna; Junttila, Kristiina
Abstract: Aims: To explore the effectiveness of a new perioperative practice model on anxiety and health‐related quality of life in patients undergoing total hip arthroplasty and total knee arthroplasty under spinal anaesthesia. Design: A randomized clinical trial. Methods: Control group participants ( N = 222) received standard perioperative care, meaning they were cared for by various nurses during their perioperative process without postoperative visits. Intervention group participants ( N = 231) were assigned one named anaesthesia nurse during their entire perioperative process who visited them postoperatively. Both groups responded to two self‐reported questionnaires: the generic 15D health‐related quality of life instrument and the State‐Trait Anxiety Inventory (STAI) measuring anxiety two to three weeks pre‐operatively and three months postoperatively. Results: There were no statistically significant differences between the groups at baseline or at follow‐up in health‐related quality of life or anxiety.